Expression of codon optimized genes in microbial systems: current industrial applications and perspectives - Elena, Claudia; Ravasi, Pablo; Castelli, Maria E.; Peiru, Salvador; Menzella, Hugo G. (Frontiers in Microbiology, 2014)
The efficient production of functional proteins in heterologous hosts is one of the major bases of modern biotechnology. Unfortunately, many genes are difficult to express outside their original context. Due to their apparent “silent” nature, synonymous codon substitutions have long been thought to be trivial. In recent years, this dogma has been refuted by evidence that codon replacement can have a significant impact on gene expression levels and protein folding. In the past decade, considerable advances in the speed and cost of gene synthesis have facilitated the complete redesign of entire gene sequences, dramatically improving the likelihood of high protein expression. This technology significantly impacts the economic feasibility of microbial-based biotechnological processes by, for example, increasing the volumetric productivities of recombinant proteins or facilitating the redesign of novel biosynthetic routes for the production of metabolites. This review discusses the current applications of this technology, particularly those regarding the production of small molecules and industrially-relevant recombinant enzymes. Suggestions for future research and potential uses are provided as well.